Problem Analysis of Online Based User Education at IAIN Kudus Library During Covid-19 Pandemic - Radiya Wira Buwana (Institut Agama Islam Negeri Salatiga, 2021)
Through the research in this paper, the author analyzes the problems that arise during the implementation of online-based user education activities at the IAIN Kudus Library. This research was conducted with a qualitative research approach. The data collection method is carried out in two ways, namely non-systematic observation and using the library research method. The method of collecting data through library research is a method of collecting data through books and journal articles which according to the author can support the discussion in this paper. The results of this study indicate that the main problem in online-based user education activities at the IAIN Kudus Library during the pandemic is the problem of information literacy skills, communication problems, and technical problems. The results obtained in this study are expected to be an input, especially for the IAIN Kudus Library and other libraries in general in carrying out user education activities in the future.